INDICATORS IN THE ECONOMIC FIELD OF STUDYING THE EFFECTIVENESS OF FOREIGN POLICY (Conferencea, 2023)
The article analyzes a group of economic indicators for researching the effectiveness of foreign policy. Relevance and importance of economic indicators are scientifically and practically justified with the help of examples.